"If I Take My Medicine, I Will Be Strong: " Evaluation of a Pediatric HIV Disclosure Intervention in Namibia. (1st January 2015) - O'Malley, Gabrielle; Beima-Sofie, Kristin; Feris, Larissa; Shepard-Perry, Mark; Hamunime, Ndapewa; John-Stewart, Grace; Kaindjee-Tjituka, Francina; Brandt, Laura
Abstract : Background: Despite known benefits, only a small proportion of HIV-infected children in sub-Saharan Africa know their status and limited disclosure interventions exist. Namibia's Ministry of Health and Social Services developed and implemented a multipronged intervention to support health care workers (HCWs) and caregivers in the disclosure process. Methods: The intervention included a staged disclosure cartoon book, child and caregiver readiness assessment tools, a monitoring form to track progress over visits, and HCW training curriculum. We conducted qualitative interviews with 35 HCWs and 46 caregivers of HIV-positive children at 4 high volume HIV clinics. Interviews elicited detailed information about intervention uptake and impact. HCWs also participated in a self-efficacy survey. Results: The intervention improved HCW and caregiver confidence and communication skills in pediatric disclosure. The most valuable intervention component was the disclosure cartoon book, which provided structure, language, and guidance for a gradual disclosure process. HCWs reported it greatly reduced caregiver resistance to disclosure. Both caregivers and HCWs reported improved knowledge and ability to support the pediatric patient, improved child understanding of how HIV medications work, increased child hopefulness for their future, and improved child adherence to care and treatment. HCW self-efficacy surveys found that HCWs who received training felt more confident in their ability to engage in the disclosure process. Conclusions: HCWs and caregivers highly endorsed the intervention. Given the urgency to address pediatric HIV disclosure in Africa, and the utility and low cost of the locally-produced disclosure tool, this approach may be useful in other similar settings.